A leitura na escola: o avesso da avaliação externa - Saionara Lucia Fonseca Murta (2004)
This research aimed at establishing relationships between reading activities developed in the classrooms of schools from the municipal chain of Belo Horizonte and the result of the assessment of SIMAVE 2002 (Sistema Mineiro de Avaliação da Educação Pública), in Brazilian Portuguese Language, in two schools with different performances in this assessment. These schools reading activities were observed for a semester. Two classes were considered as weak and as strong ones, in each one of them, we assume that an external assessment does not take into account the specificities of each school. These classes are from the second phase of the second Ciclo de Formação (Formation Cycle) (which corresponds to the 4th grade of Ensino Fundamental (Primary School)). Some analysis categories have been established to compare reading activities developed in classes and subjects which were followed-up, as their way of reading texts, the characteristics of the textual material, reading activities carried out by the students, the skills present at these activities and the pedagogical practice carried out in each class. As a result of these observations, we may state that reading practices were similar among the classes followed-up regarding their ways of reading, characteristics of the textual material and reading activities and skills, with some differences in reading interventions and strategies proposed by teachers. The skills measured by SIMAVE assessment. Thus, some hypotheses have been formulated to explain obtaining distinct results by two schools in an external assessment, which measures reading skills, such as difference in schools socio- economical level and the difference in the reading learning level among the classes.